LY53857, a 5HT2 Receptor Antagonist, Delays Occlusion and Inhibits Platelet Aggregation in a Rabbit Model of Carotid Artery Occlusion - Wilson, Harve C; Coffman, William; Killam, Anne L; Cohen, Marlene L (Thrombosis and Haemostasis, 1991)
The present study was designed to evaluate the effectiveness of the ergoline 5HT2 receptor antagonist, LY53857 in a rabbit model of vascular arterial occlusion. LY53857 (1 and 10 εM) inhibited serotonin amplified platelet aggregation responses to threshold concentrations of ADP in rabbit platelets in vitro. LY53857 (1 εM) not only inhibited the serotonin component of rabbit platelet aggregation, but also inhibited in vitro aggregation induced by ADP (48.7 ± 16.7% inhibition), collagen (76.1 ± 15.9% inhibition) and U46619 (65.2 ± 12.3% inhibition). The effectiveness of this ergoline 5HT2 receptor antagonist in blocking aggregation to ADP, collagen and U46619 may be related to its ability to inhibit a serotonin component of platelet aggregation since rabbit platelets possess high concentrations of serotonin that may be released during aggregation produced by other agents. Based on the effectiveness of LY53857 to inhibit rabbit platelet aggregation, we explored the ability of LY53857 to extend the time to carotid artery occlusion in rabbits following electrical stimulation of the artery. Reproducible carotid artery occlusion was induced in rabbits by moderate stenosis coupled to arterial cross clamping, followed by electrical stimulation. With this procedure, occlusion occurred at 47.0 ± 7 min (n = 30) after initiation of the electrical stimulation. Animals pretreated with LY53857 (50 to 500 εg/kg i.v.) showed a delay in the time to carotid artery occlusion (at 100 εg/kg i.v. occlusion time extended to 164 ± 16 min). Furthermore, ex vivo platelet aggregation from animals treated with LY53857 (300 εg/kg i.v.) resulted in 40.5% inhibition of platelet aggregation in response to the combination of ADP (1 εM) and serotonin (1 εM). These studies document the ability to obtain reproducible arterial occlusion in the rabbit and showed that intravenously administered LY53857 prolonged the time to carotid artery occlusion. Prolongation of carotid artery occlusion time was accompanied by inhibition of serotonin-amplified ADP-induced aggregation in rabbit platelets, an effect observed both in vitro and ex vivo. Thus, the rabbit is a useful model for studying the effectiveness of 5HT2 receptor antagonists in prolonging vascular occlusion induced by insult of the carotid artery.